Human Security: Virtuous, Practical, Urgent, and Necessary - Jonathan Granoff (Cadmus, 2023)
Change is urgently needed. Ideas that can generate change are critical at this time and age where humanity is facing multidimensional crises that are characterised by complexity. Human security is that idea that can help us address the crises in their entirety because it‘s comprehensive, integrative, people-centered and goes beyond conventional disciplines and borders. We urgently need a global cooperative security system to pursue security which focuses on the well being of the people and the planet, not one at the expense of the other; and, never puts the security of people second to the concept of the security of the state. Continuing without the compelling and the much-needed paradigm change that Human Security is, will only lead to disaster.